Ketamine Infusion for Sedation and Analgesia during Mechanical Ventilation in the ICU: A Multicenter Evaluation - Kathryn M. Pendleton; Laurel E. Stephenson; Nick Goeden; Anna R. Benson; Qi Wang; Salman B. Mahmood; Kelly A. Considine; Matthew E. Prekker (Critical Care Research and Practice)
Rationale. Ketamine can provide dissociative sedation and analgesia for mechanically ventilated ICU patients, yet it has been utilized less than other drugs for this purpose. Methods. We reviewed the electronic medical record of critically ill adults who received a continuous infusion of ketamine for ≥24 hours during invasive mechanical ventilation in three hospitals over a two-year period. We captured data including ketamine indication, dose, unintended effects, and adjustments to coadministered sedatives or opioids. We analyzed these data to determine the incidence of reported unintended effects of ketamine infusion (primary outcome) and changes in exposure to coadministered sedatives or opioids during ketamine use (secondary outcome). Results. 95 mechanically ventilated adults received a ketamine infusion for a median duration of 75 hours (interquartile range [IQR] 44–115) at a mean ± standard deviation (SD) infusion rate of 1.3 ± 0.5 mg/kg/hour for the first 24 hours. At least one unintended effect attributed to ketamine was documented in 24% of cases, most frequently tachycardia (6%) and sialorrhea (6%). Other sedative or opioid infusions were administered with ketamine in 76% and 92% of cases, respectively. Comparing the total amount of sedative or opioid administered in the 24 hours prior to ketamine infusion with the total amount administered during the first 24 hours on ketamine, there were no significant differences in propofol, midazolam, or dexmedetomidine exposure, but the average fentanyl exposure was higher after ketamine (2740 ± 1812 mcg) than before (1975 ± 1860 mcg) (absolute difference 766 mcg, 95% confidence interval [CI] 442 to 1089 mcg). Conclusions. In this multicenter cohort of critically ill, mechanically ventilated adults, ketamine infusion was primarily used as an adjunct to conventional sedative and opioid infusions, with noticeable but unintended effects potentially related to ketamine in nearly one-quarter of cases.